A new definition and refocus of pharmaceutical care: the Barbate Document - Ramón Morillo-Verdugo; José Luis Poveda-Andrés; María de las Aguas Robustillo-Cortés; Miguel Ángel Calleja-Hernández (Farmacia Hospitalaria)
Objective: To propose an updated definition of Pharmaceutical Care based on the Capacity-Motivation-Opportunity (CMO) model and on the key elements and optimal activities for its development that guarantee the highest levels of quality and excellence in this professional activity. Method: The consensus was developed by a working group composed of members of the Spanish Society of Hospital Pharmacy and other pharmacists from different healthcare fields. A literature review of PubMed was conducted of the available scientific evidence on pharmaceutical healthcare models and activities with the greatest impact and ease of implementation. A working definition was developed and the initiatives chosen as key elements were collected and included in each pillar of the proposed model. After creating an initial list of activities and terms, the working group reviewed it and made corrections or proposed new activities. In addition, the definitions of the three key elements of the CMO model were agreed upon: Capacity-Motivation- Opportunity. In order to incorporate all appropriate suggestions and contributions before finalizing the consensus, the final draft was sent to the different scientific, pharmaceutical, and medical societies as well as patient associations with which the Spanish Society of Hospital Pharmacy has a collaboration agreement. Results: The definition of consensual Pharmaceutical Care was “Any professional activity by which the pharmacist is linked to the patient (and/or caregiver) and other healthcare professionals, to attend to the patient according to their needs, setting out strategies to align and achieve the shortand medium-/long-term objectives of pharmacotherapy and incorporating new technologies and the means available to continuously interact with ment was reached on the definitions of the three key elements of the CMO model. Finally, 27 key elements for the development of pharmaceutical activity were identified and included in the three pillars of the model. Conclusions: A new definition of Pharmaceutical Care has been agreed upon that refocuses this professional activity, allowing us to advance within the multidisciplinary working approach toward a longitudinal and multidimensional approach to the patient.